2021
DOI: 10.1038/s42003-021-01964-y
|View full text |Cite
|
Sign up to set email alerts
|

Sweet taste of heavy water

Abstract: Hydrogen to deuterium isotopic substitution has only a minor effect on physical and chemical properties of water and, as such, is not supposed to influence its neutral taste. Here we conclusively demonstrate that humans are, nevertheless, able to distinguish D2O from H2O by taste. Indeed, highly purified heavy water has a distinctly sweeter taste than same-purity normal water and can add to perceived sweetness of sweeteners. In contrast, mice do not prefer D2O over H2O, indicating that they are not likely to p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 56 publications
8
24
0
Order By: Relevance
“…4,5 On a safer note, we have recently confirmed old claims that heavy water has a mildly but distinctly sweet taste, showing that D 2 O (unlike H 2 O) activated the human sweet taste receptor. 6 While the exact molecular mechanism of the sweet taste of D 2 O remains elusive, our simulations confirm experimental observations that in general protein stability and rigidity change (typically slightly increase) upon moving from ordinary to heavy water. 7−9 Changes in protein behavior in ordinary vs heavy water are primarily due to differences in hydrogen bonding due to NQEs; 3 namely, a reduction in vibrational zero-point energies leads to slightly stronger water−water and water−protein hydrogen bonds in D 2 O vs H 2 O.…”
Section: ■ Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…4,5 On a safer note, we have recently confirmed old claims that heavy water has a mildly but distinctly sweet taste, showing that D 2 O (unlike H 2 O) activated the human sweet taste receptor. 6 While the exact molecular mechanism of the sweet taste of D 2 O remains elusive, our simulations confirm experimental observations that in general protein stability and rigidity change (typically slightly increase) upon moving from ordinary to heavy water. 7−9 Changes in protein behavior in ordinary vs heavy water are primarily due to differences in hydrogen bonding due to NQEs; 3 namely, a reduction in vibrational zero-point energies leads to slightly stronger water−water and water−protein hydrogen bonds in D 2 O vs H 2 O.…”
Section: ■ Introductionsupporting
confidence: 74%
“…The above differences between ordinary and heavy water, in particular kinetic effects concerning proton/deuteron transfer, are behind the very low toxicity of D 2 O to higher organisms, which only becomes an issue if a sizable amount (tens of percent) of bodily water is replaced by its deuterated analogue. , On a safer note, we have recently confirmed old claims that heavy water has a mildly but distinctly sweet taste, showing that D 2 O (unlike H 2 O) activated the human sweet taste receptor . While the exact molecular mechanism of the sweet taste of D 2 O remains elusive, our simulations confirm experimental observations that in general protein stability and rigidity change (typically slightly increase) upon moving from ordinary to heavy water. …”
Section: Introductionsupporting
confidence: 60%
“…In a fully controlled experiment, unlike the 1935 paper with an N = 2, blinded human participants reportedly ranked D 2 O as more sweet than H 2 O. 13 Dr. Niv's group tracked this perception down to the sweet taste receptor homodimer T1R2/T1R3 using clever in vivo pharmacology. This was backed up with in vitro assays in transfected cells that further demonstrated that T1R2/T1R3 is activated by D 2 O.…”
Section: ■ Session 2: Structural Biologymentioning
confidence: 99%
“…However, chemists, with perhaps questionable lab safety protocols, have repeatedly claimed that D 2 O tastes sweet. In a fully controlled experiment, unlike the 1935 paper with an N = 2, blinded human participants reportedly ranked D 2 O as more sweet than H 2 O . Dr. Niv’s group tracked this perception down to the sweet taste receptor homodimer T1R2/T1R3 using clever in vivo pharmacology.…”
Section: Keynote 1: Masha Niv Hebrew Institute Of Jerusalemmentioning
confidence: 99%
“…There have been many theoretical developments on the incorporation of NQEs in molecular simulations. Some empirical force fields [6] have been used to include NQEs implicitly, and have been able to treat protons and deuteriums differently in water [7]. Quantum wave packet dynamics is based on the exact time evolution of a quantum system according to the time-dependent Schrödinger equation and can give theoretical predictions that accurately match to experiments [8][9][10][11][12].…”
mentioning
confidence: 99%